The affinity of magnetic microspheres for Schistosoma eggs. Issue 1 (January 2015) - Candido, Renata R.F.; Favero, Vivian; Duke, Mary; Karl, Stephan; Gutiérrez, Lucía; Woodward, Robert C.; Graeff-Teixeira, Carlos; Jones, Malcolm K.; St. Pierre, Timothy G.
Graphical abstract: Highlights: Schistosoma eggs physically bind magnetite-coated polystyrene microspheres. Schsitosoma japonicum eggs have greater affinity for magnetic microspheres than S. mansoni . There are two groups of Schistosoma eggs, one binds weakly and the other, strongly. Source of binding could be differences in zeta potentials between eggs and spheres. Abstract: Schistosomiasis is a chronic parasitic disease of humans, with two species primarily causing the intestinal infection: Schistosoma mansoni and Schistosoma japonicum . Traditionally, diagnosis of schistosomiasis is achieved through direct visualisation of eggs in faeces using techniques that lack the sensitivity required to detect all infections, especially in areas of low endemicity. A recently developed method termed Helmintex™ is a very sensitive technique for detection of Schistosoma eggs and exhibits 100% sensitivity at 1.3 eggs per gram of faeces, enough to detect even low-level infections. The Helminthex™ method is based on the interaction of magnetic microspheres and schistosome eggs. Further understanding the underlying egg-microsphere interactions would enable a targeted optimisation of egg-particle binding and may thus enable a significant improvement of the Helmintex™ method and diagnostic sensitivity in areas with low infection rates. We investigated the magnetic properties of S. mansoni and S. japonicum eggs and their interactions with microspheres with different magnetic properties and surface functionalization. Eggs of both species exhibited higher binding affinity to the magnetic microspheres than the non-magnetic microspheres. Binding efficiency was further enhanced if the particles were coated with streptavidin. Schistosoma japonicum eggs bound more microspheres compared with S. mansoni . However, distinct differences within eggs of each species were also observed when the distribution of the number of microspheres bound per egg was modelled with double Poisson distributions. Using this approach, both S. japonicum and S. mansoni eggs fell into two groups, one having greater affinity for magnetic microspheres than the other, indicating that not all eggs of a species exhibit the same binding affinity. Our observations suggest that interaction between the microspheres and eggs is more likely to be related to surface charge-based electrostatic interactions between eggs and magnetic iron oxide rather than through a direct magnetic interaction.